Perjanjian Buruh Pati Antara Pengusaha dengan Buruh dalam Konteks Omnimbus Law: Pati Labor Agreement between Employers and Workers in the Context of Omnibus Law - Permadi, Sandro Wahyu; Krismawan, Deny Andreas (Warkat, 2021)
The world economy moves based on human needs and the system of organization within a space of countries. The economy cannot escape business activities that arise from the processing of raw materials into ready-to-use materials. There is often overlap between employers and workers regarding agreements given by companies to their employees which are one-sided and do not provide a portion of human rights. This research aims to analyze the protection of workers' rights and obligations in employment based on the Omnimbus law perspective and the extent of the effectiveness of the implementation of the Omnimbus law on the Labor Law. This research uses normative research methods with a statutory approach and an analytical approach. The results obtained from this research are that the work copyright omnimbus does not provide guarantees for the protection of the rights and obligations of workers so that many workers' rights are not fulfilled and protected. Then the implementation of the work copyright omnimbus law is less effective in providing protection for workers and laborers, so a change is needed in regulations based on progressive law that pays attention to the structure, substance and culture of a regulation so as to provide maximum benefits for employers, workers and the government.